(untitled) (Al-Qamar, 2025)
This research provides a comprehensive analytical study of the modes of Islamic financing (ṭuruq al-tamwīl al-islāmī) practiced by Islamic banks in Pakistan. It examines how classical Sharīʿah-based contractual models—such as Murābaḥah (cost-plus financing), Ijārah (leasing), Mushārakah (partnership), and Muḍārabah (profit-sharing)—have been adapted and operationalized within the modern banking framework. The study seeks to evaluate both the conceptual authenticity and practical implementation of these modes in light of Qur’anic principles, Prophetic traditions, and juristic consensus (ijmāʿ). Using a descriptive-analytical and comparative methodology, the research analyzes official documents, regulatory frameworks, and financial data from leading Islamic banks in Pakistan, including Meezan Bank, BankIslami, and Dubai Islamic Bank. It investigates whether the operational mechanisms of these institutions truly embody the ethical and risk-sharing spirit of Islamic finance or whether they merely replicate conventional banking structures under Sharīʿah-compliant nomenclature. The paper further discusses key challenges confronting the Islamic banking sector in Pakistan—such as standardization of Sharīʿah rulings, liquidity management, risk diversification, and public perception regarding the authenticity of Islamic products. It also highlights recent initiatives by the State Bank of Pakistan and Sharīʿah Advisory Boards in refining regulatory practices and ensuring compliance with international Sharīʿah standards (AAOIFI, IFSB). Ultimately, the study argues that genuine Islamization of finance demands more than formal Sharīʿah compliance; it requires a value-oriented transformation in institutional ethics, contractual transparency, and socio-economic objectives. The evolution of Islamic financing in Pakistan thus stands at a critical juncture—between doctrinal fidelity and practical exigency—reflecting the broader struggle to reconcile divine injunctions with modern financial realities.